2022
DOI: 10.2174/1573405617666210623124108
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Low-dose Chest CT Acquisition Protocol for the Imaging of COVID-19 Pneumonia

Abstract: Objective: To investigate the feasibility of low dose chest CT acquisition protocol for the imaging of either the confirmed case of COVID-19 disease or the suspected case of this disease in adults. Method: In this retrospective case-control study, the study group consisted of 141 patients who were imaged with low dose chest CT acquisition protocol. The control group consisted of 92 patients who were imaged with the standard protocol. Anteroposterior and lateral diameters of chest, effective diameter and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this current study, 23,7% of the respondents stated that the dedicated Covid-19 chest CT protocol differed from the standard by radiation dose, kV and mAs (10.2%) and by using a high resolution CT (HRCT) protocol (56.3%). Atli E. et al [11] confirmed that a lowdose chest CT protocol intended for Covid-19 pneumonia did not affect the image quality or the diagnostic confidence. Additionally, regarding dedicated portable x-ray machine for CXR on patients with Sars-Cov-2 infection, statistical relevance (p value < 0,001) was recorded.…”
Section: Discussionmentioning
confidence: 92%
“…In this current study, 23,7% of the respondents stated that the dedicated Covid-19 chest CT protocol differed from the standard by radiation dose, kV and mAs (10.2%) and by using a high resolution CT (HRCT) protocol (56.3%). Atli E. et al [11] confirmed that a lowdose chest CT protocol intended for Covid-19 pneumonia did not affect the image quality or the diagnostic confidence. Additionally, regarding dedicated portable x-ray machine for CXR on patients with Sars-Cov-2 infection, statistical relevance (p value < 0,001) was recorded.…”
Section: Discussionmentioning
confidence: 92%
“…Several CT protocols for diagnosing and monitoring the course of COVID-19 and its treatment have been published since the beginning of the pandemic for a variety of CT scanners and vendors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Quite often, protocols vary with regard to the associated radiation exposure and the desired image quality (IQ).…”
Section: Introductionmentioning
confidence: 99%